A kinematic conservation law in free surface flow. (14th May 2015) - Gavrilyuk, Sergey; Kalisch, Henrik; Khorsand, Zahra
Abstract: The Green–Naghdi system is used to model highly nonlinear weakly dispersive waves propagating at the surface of a shallow layer of a perfect fluid. The system has three associated conservation laws which describe the conservation of mass, momentum, and energy due to the surface wave motion. In addition, the system features a fourth conservation law which is the main focus of this note. It will be shown how this fourth conservation law can be interpreted in terms of a concrete kinematic quantity connected to the evolution of the tangent velocity at the free surface. The equation for the tangent velocity is first derived for the full Euler equations in both two and three dimensional flows, and in both cases, it gives rise to an approximate balance law in the Green–Naghdi theory which turns out to be identical to the fourth conservation law for this system. It is also shown that the conservation equation for the tangent velocity at the free surface appears as an endpoint case of a more general conservation equation for tangent velocities along material surfaces in the body of the fluid.